The Contribution of Adaptive Instructional Design in Enhancing Students’ Self-Confidence in Junior High School Speaking Activities in Bengkalis Regency - Chantika, Faradila; Mahdum; Supriusman (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study aims to investigate the contribution of adaptive instructional design in enhancing students’ self-confidence in speaking activities at the junior high school level in Bengkalis Regency, Indonesia. Self-confidence is a key psychological factor that influences students’ willingness to actively participate in oral communication. The research employed a quasi-experimental design involving two groups: an experimental group (taught with adaptive instructional strategies) and a control group (taught using conventional methods). A validated self-confidence questionnaire was administered as the main instrument, and data were analyzed using descriptive statistics and an independent sample t-test. The results revealed that the experimental group achieved a higher mean score (M = 78.65, SD = 6.42) compared to the control group (M = 70.12, SD = 7.11), with a statistically significant difference (t(58) = 3.47, p < 0.01). These findings highlight that adaptive instructional design—when tailored to students’ learning needs and characteristics—plays a crucial role in fostering psychological readiness and communicative competence. This study suggests that adaptive learning strategies can be effectively integrated into language teaching to create a supportive and engaging environment for students.